1992
DOI: 10.2166/wst.1992.0135
|View full text |Cite
|
Sign up to set email alerts
|

Acidogenesis in Relation to In-Reactor Granule Yield

Abstract: A systematic study of in-reactor granule yield data was set up in the laboratory. Methanogenic granular sludge growth in fed batch shake flasks for different substrates appeared to decrease with the energy content of the substrate and required the presence of a mixing force. In UASB reactors, granular cell yields were found to be quite variable suggesting the involvement of complex microbiological interactions. The factor foremost in influencing the build-up in the reactor of granular sludge was the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 0 publications
3
37
0
Order By: Relevance
“…The data showed that even with different batches of anaerobic sludge, characteristic acetic and propionic acid and pH profiles were obtained and that, when using lactate as a carbon source, a repeatable metabolic pathway could be obtained. It is also known that propionate producers are effective ECP and aggregate formers (Mulder et al, 1989;Riedel and Britz, 1993;Slobodkin and Verstraete, 1993) and the formation of extracellular polysaccharides may serve as an alternative hydrogen sink mechanism for the propionate producers (Quarmby and Forster, 1995;Vanderhaegen et al, 1992). The results obtained and the increase in the formation of granules indicated that granulation could be enhanced in batch systems, and that a drop in pH at the start appears to facilitate the process.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The data showed that even with different batches of anaerobic sludge, characteristic acetic and propionic acid and pH profiles were obtained and that, when using lactate as a carbon source, a repeatable metabolic pathway could be obtained. It is also known that propionate producers are effective ECP and aggregate formers (Mulder et al, 1989;Riedel and Britz, 1993;Slobodkin and Verstraete, 1993) and the formation of extracellular polysaccharides may serve as an alternative hydrogen sink mechanism for the propionate producers (Quarmby and Forster, 1995;Vanderhaegen et al, 1992). The results obtained and the increase in the formation of granules indicated that granulation could be enhanced in batch systems, and that a drop in pH at the start appears to facilitate the process.…”
Section: Discussionmentioning
confidence: 88%
“…Vanderhaegen et al (1992) showed in growth studies with granules in batch cultures that the factor foremost in influencing the build-up in the reactor of granular sludge was the presence of highenergy sugars (Thaveesri et al, 1994). For this study, glucose (Lens et al, 1993), sucrose (Quarmby and Forster, 1995) and lactate (Riedel and Britz, 1993) were selected as carbon sources that have been reported to be granulation enhancers.…”
Section: Resultsmentioning
confidence: 99%
“…Besides Methanosaeta nuclei, researchers have hypothesized that nuclei for granulation may consist of fermenting bacteria (Jhung and Choi, 1995;Mulder et al, 1989;Vanderhaegen et al, 1992), Methanosarcina spp. (Grotenhuis et al, 1987;Wu et al, 1996), and syntrophic consortia (El-Mamouni et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The small differences in the mean diameter of the sludges sampled on days 295, 350 and 393 of the bottom and the top (Table 5.1.5, mean diameter) are probably due to the mixing of granules over the sludge bed on the long term (295 days). So, for instance overloading of the module II in period IV (average OLR for second stage was 7.9 kg COD m" The strength of the granules in the module I initially increased (Table 5. 1.5), possibly as a result of the fast additional formation of extracellular polymers inside the granules (Vanderhaegen et al, 1992). However, later the strength of the granules dropped, probably due to the formation of an attached fluffy acidifying layer .…”
Section: Biomass Characteristicsmentioning
confidence: 97%
“…The increase of the apparent Y^ of the sludge in module I at days 234 and 393 compared to days 295 and 350 (Table 5. 1.4, 5.1.5), might be attributed to the formation of extracellular polymers (Vanderhaegen et al, 1992;Bhatti et al, 1995), or to extensive growth of acidifying bacteria on the surface of methanogenic granules . Interestingly, the observed increase in K^ was accompanied by a severe drop in the apparent diffusion coefficient (Table 5. 1.5).…”
Section: Biomass Characteristicsmentioning
confidence: 99%